Modernism and Public Reform in Late Imperial Russia - Gerasimov, I. author. aut Link
X, 325 p. 1 illus.
Keywords: This book is a comprehensive reconstruction of the successful attempt by rural professionals in late imperial Russia to engage peasants in a common public sphere. Covers a range of aspects, from personal income and the dynamics of the job market to ideological conflicts and psychological transformation. Based on hundreds of individual life stories.